Effect of hypoosmotic environment on canine semen sperm viability - Sánchez R., Alfonso (2016)
The hypoosmotic test is widely used for determining sperm quality in several animal species. The present study aimed to compare the effect of incubation of canine sperm into two hypoosmotic solutions (0 mOsm/l - HOST-s and 150 mOsm/l - HOST) on sperm viability. Fifteen ejaculates (2nd fraction) were obtained by digital manipulation from 10dogs and the spermiograms were considered as normals. A 5 μl aliquots per ejaculate were diluted in 45 μl of each of the two hypoosmotic solutions and incubated at 37 °C for 5 and 45 min respectively. Sperm viability was assessed using eosin-nigrosin staining. Results of the hypoosmotic test were 92.1 and 90.1% of dilated spermatozoa for HOST-s and HOST respectively (p<0.05) and the sperm viability was 66.5 and 78.3% of live spermatozoa for HOST-s and HOST respectively (p<0.01). It was concluded that thelower osmolality generates lower sperm viability post-incubation.